Vitality of the sexagesimal system - Paliokas, Eugenijus (Lietuvos matematikos rinkinys, 2012)
Some aspects in teaching mathematics are observed for the purpose of revitalizing mathematics adding historical and semantic points of view. Hypothesis of arrising of the sexagesimal system is presented.